2014
DOI: 10.1039/c4tb01139b
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon-photosensitizer resonance coupling: an enhanced singlet oxygen production platform for broad-spectrum photodynamic inactivation of bacteria

Abstract: A general platform to improve singlet oxygen productionviaresonance coupling between surface plasmon and photosensitizers, and for broad-spectrum photodynamic inactivation of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 61 publications
6
52
0
Order By: Relevance
“…As shown in Figure , the riboflavin‐containing hybrid has a much higher singlet oxygen production than free riboflavin or PDDA‐coated AgNPs, separately, under 446 nm excitation, with an enhancement factor of ∼14.6. This observation is consistent with our previous work involving a different photosensitizing molecule . More strikingly, significant singlet oxygen production can also be observed from the same hybrid under 880 nm (near‐infrared) excitation, where free riboflavin molecules do not produce singlet oxygen.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As shown in Figure , the riboflavin‐containing hybrid has a much higher singlet oxygen production than free riboflavin or PDDA‐coated AgNPs, separately, under 446 nm excitation, with an enhancement factor of ∼14.6. This observation is consistent with our previous work involving a different photosensitizing molecule . More strikingly, significant singlet oxygen production can also be observed from the same hybrid under 880 nm (near‐infrared) excitation, where free riboflavin molecules do not produce singlet oxygen.…”
Section: Resultssupporting
confidence: 92%
“…We have previously demonstrated that plasmon‐photosensitizer hybrids display potent efficacy in broad‐spectrum PDI of bacteria, including gram‐positive, gram‐negative, and even drug‐resistant bacteria . Inspired by the broadened excitation profiles of these plasmon‐photosensitizer hybrids observed spectroscopically, we examined their efficacy in inactivating bacteria upon the irradiation with near‐infrared and visible light, respectively (Figures S3–S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach proved to be successful, and both Ag and Au MNPs coated with mesoporous silica shells loaded with photosensitizers exhibit an enhancement of 1 O 2 production. [135,136] A potential drawback of this strategy is that 1 O 2 has to diffuse outside the silica matrix in order to have any potential use. [137] To alleviate this difficulty, an alternate approach would be to covalently attach the photosensitizer onto the MNPs surface.…”
Section: Metallic Nanoparticles As Photosensitizer Carriersmentioning
confidence: 99%